MENEMUKAN AKAR PERSAMAAN POLINOMIAL MENGGUNAKAN PARTICLE SWARM OPTIMIZATION - Darmawan, Oei, Edwin Wicaksono; Antonius, Suyanto Edward (Universitas Katolik Soegijapranata, 2017)
Polynomial is a mathematic function which involves multiplication, exponent, and variable. There are some methods to find the root of the function. The method will be more complicated if the highest exponent of the function is 3 or greater. This project will solve the problem using Particle Swarm Optimization algorithm to find the root with an accurate number